A Hierarchical Model of Coping in the College Student Population - Pickens, Bryon C.; Mckinney, Robert; Bell, Stephanie C. (Journal of Interdisciplinary Studies in Education, 2019)
Research has indicated a fall in college student mental health over the past 16 years, with no corresponding increase in use of mental health care services. To investigate how college students choose to manage stressful issues, we assessed coping styles as measured by the dispositional COPE inventory in a multi-state sample of undergraduate students (N = 109).We tested a four-factor, hierarchical model of coping with a factor-based variant of partial least squares structural equation modeling (PLS-SEM), an approach noted for its accuracy with small sample sizes. Results indicated the existence of a hierarchical effect that explained 67.4 percent of variance in coping subscale scores, and validated the four factors of Approach, Avoidance, Social-Contextual, and Individual-Contextual coping styles. All coping style pairs had significant positive relationships (p < .002) with one exception; Approach and Avoidance had a significant negative relationship (p < .001).  Implications for researchers and practitioners are discussed.